Alterations in novel inflammatory biomarkers during perioperative cardiovascular surgeries involving cardiopulmonary bypass: a retrospective propensity score matching study - Zhou, Wei; Wang, He; Li, Chen; Ma, Qi-min; Gu, Yan-hui; Sheng, Shu-yue; Ma, Shao-lin; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiopulmonary bypass (CPB) triggers a strong inflammatory response in cardiovascular surgery patients during the perioperative period. This article mainly focuses on the perioperative application of novel inflammatory biomarkers in cardiovascular surgeries involving CPB. Methods Patients were divided into a CPB group and a non-CPB group according to whether they underwent CPB during cardiovascular surgery. Novel inflammatory biomarkers and clinical results were recorded. The neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), platelet × neutrophil/lymphocyte ratio (SII), and monocyte × platelet × neutrophil/lymphocyte ratio (PIV) were calculated. The primary outcomes were perioperative prognosis between the CPB and non-CPB groups. The secondary outcomes included perioperative alterations of novel inflammatory biomarkers in the CPB group and predictive values of novel inflammatory biomarkers for postoperative infection and acute kidney injury. Results A total of 332 patients were initially included in the study. Before propensity score matching (PSM), there were 96 patients in the CPB group and 236 patients in the non-CPB group. After PSM, both groups included 58 patients each. Compared with the non-CPB group, the CPB group had a higher proportion of intraoperative transfusion of blood products (63.79% vs. 6.90%, P < 0.001), specifically for red blood cells (58.62% vs. 3.45%, P < 0.001) and plasma (41.38% vs. 1.72, P < 0.001), exhibited a higher drainage fluid volume within 24 h [380 (200–550) ml vs. 200 (24–330) ml, P = 0.002], and required longer durations of mechanical ventilation [14.3 (6.6–21.3) h vs. 5.75 (4.08–10.1) h, P < 0.001] and ICU stay [48.78 (44.92–89.38) h vs. 27.16 (21.67–46.25) h, P < 0.001]. After surgery, NLR [14.00 (9.93–23.08) vs. 11.55 (7.38–17.38), P = 0.043] was higher in the CPB group, while the PIV, PLR, and SII in the CPB group were lower than those in the non-CPB group on the first day after surgery. Conclusions Cardiovascular surgeries involving CPB exhibit a poorer prognosis compared to non-CPB procedures. Novel inflammatory biomarkers, including PLR, PIV, and SII, may offer valuable insights into the degree of postoperative inflammation, with NLR emerging as a potentially reliable prognostic indicator.